Kajian Yuridis Penegakan Hukum Terhadap Tindak Pidana Kekerasan Dalam Rumah Tangga - Fiyan Fadlyawan; Muhammad Al Habsy Ahmad (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This research aims to examine and analyze the effectiveness of law enforcement against criminal acts of domestic violence and the factors that become obstacles to law enforcement against criminal acts of domestic violence. The method used in the research is a juridical and sociological approach. The results of the research show that in this study criminal law enforcement regarding domestic violence was less effective due to the existence of several conflicting laws and regulations governing domestic violence such as Criminal Code Law Number 39 of 1999 and Law number 23 of 2004. In connection with several of the cases presented, it can be stated that the law regarding the eradication of domestic violence has only just begun to be socialized and handled well, so that the perpetrators have begun to receive appropriate punishment and the victims receive legal protection and a sense of security. as citizens and as members of society, as well as the existence of law enforcers who are not yet professional in dealing with criminal acts of domestic violence and also the public's legal awareness is still lacking, because there is still an assumption that women are under the auspices of men